Peculiar challenges of a glass object retained in rectum: review of current options - Kesiezie, Khriethonuo; Meena, Sanjay; Goel, Mahak; Sharma, Deborshi (International Surgery Journal, 2023)
Rectal foreign bodies are rare and often challenging. It can vary from soft toys to hard glass or wooden objects. Patients are mostly habitual offenders who generally present to emergency due to retained foreign body or complications like perforation or bleeding. Proper history with a plain X-ray is often enough for the diagnosis and position of the foreign body. However, management can be varied from a simple trans-anal retrieval to an exploratory laparotomy. Minimal invasive techniques also have a role in current scenario. We report an unusual glass foreign body with its opening placed caudally.